The Different Clinical Courses of Legionnaires’ Disease in Newborns from the Same Maternity Hospital - Andrijana Kostic; Katarina Cukovic; Lidija Stankovic; Zorica Raskovic; Jelena Nestorovic; Dragana Savic; Aleksandra Simovic; Tijana Prodanovic; Suzana Zivojinovic; Sladjana Andrejevic; Ismihana Erovic; Zorana Djordjevic; et al. (Medicina, 2022)
In children, the incidence of Legionnaires’ disease (LD) is unknown, hospital-acquired LD is associated with clinical risk factors and environmental risk, and children with cell-mediated immune deficiency are at high risk of infection. Both newborns were born in the same delivery room; stayed in the same hospital room where they were cared for, bathed, and breastfed; were male; were born on time, with normal birth weight, and with high Apgar score at birth; and survived this severe infection (L. pneumophila, serogroup 2-15) but with different clinical courses. In neonate 1, bleeding in the brain, thrombosis of deep pelvic veins, and necrosis of the lungs, which left behind cystic and cavernous changes in the lungs, were found, while neonate 2 suffered from pneumonia alone. The only difference in risk factors for LD between these two newborns is the number of days of illness until the start of azithromycin treatment (sixth versus the third day of illness). We suggest that a change in the guidelines for diagnosing and treating community-acquired pneumonia and hospital-acquired pneumonia in newborns is needed in terms of mandatory routine testing for Legionella pneumophila. Early initiation of macrolide therapy is crucial for the outcome of LD in the newborn.